Effect of socio-economic and demographic factors on ride-sourcing services in Dhaka City, Bangladesh. (December 2021) - Rahman, Md. Hishamur; Sadeek, Soumik Nafis; Ahmed, Asif; Rifaat, Shakil Mohammad; Abrar, Masnun
Highlights: Car and Motorcycle are popular ride-sourcing services in Dhaka City. Socio-economic and demographic factors influence on the ride-sourcing service choice. Bivariate-ordered Probit Model is used to model ride-sourcing service choices. Influence of factors vary among developed and developing countries. Gender, income, education are factors having positive impact on the choices. Abstract: Ride-sourcing services have emerged in the entire world through advancement of information technology. This service has also penetrated in the market of the developing countries similar to Bangladesh with immense potential. People have adopted this new trip concept with a hope to ease their daily lives by hassle free movement. In developed countries, making trips using ride-sourcing services have been greatly influenced by users' socio-economic and demographic backgrounds. But, it is hitherto unclear how this ride-service concept is influenced by the social and economic characteristics of the users from developing countries. Hence, this research attempts to unveil the inherent relationships between users' usage of motorcycle and car ride-sourcing services and their socio-economic and demographic backgrounds. The sample size contains responses of 1003 respondents. Sixteen questions are asked indicating different socio-economic and demographic characteristics of the respondents towards their choice between motorbike and car ride-sourcing: two most popular ride-sourcing services in Bangladesh. A Bivariate-ordered Probit Model has been used to model jointly their choices towards ride-sourcing services. The outcomes indicate that people with certain types of socio-demographic background prefer to use motorcycles over cars for ride-sourcing and vice-versa. The result also shows that gender, household density, income, educational qualification, and smart-phone usage have a propensity to increase ride-sourcing choice towards both motorbikes and cars. The outcomes are expected to provide useful insights to the ride-sourcing service providers, transport agencies and policy makers of Bangladesh in understanding the choice behaviors from the ride-sourcing user perspectives.